2019
DOI: 10.1088/1742-6596/1294/5/052047
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Relationship between Interleukins 17, 37 and 38 with Vitamin E in Iraqi Men with CHB.

Abstract: Hepatitis B is a possibly life-threatening liver contagion produced by the hepatitis B virus (HBV). It is a main worldwide health issue. It can cause chronic contagion & puts societies at great danger of death from cirrhosis & liver malignancy. The goal of the current research was to measure four important parameters in cases with chronic hepatitis B (CHB) (the amount of IL-17, IL-37, IL-38 & vitamin E). These factors were surveyed in CHB patients to compare with healthy controls & study the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Gao et al 49 revealed that the level of IL‐38 and IL‐36α was significantly elevated in patients with influenza and COVID‐19, in which IL‐38 level was negatively and IL‐36α was positively associated with infection severity. Wang et al 50 showed elevated level of IL‐38 in patients with chronic hepatitis B, suggesting that IL‐38 could be used as a biomarker for liver hepatitis infection and liver injury 51 . Fazeli et al 52 reported that the level of IL‐38 was higher in healthy subjects than treated HCV‐infected patients, and HCV‐infected patients with higher levels of IL‐38 indicated less liver damage.…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al 49 revealed that the level of IL‐38 and IL‐36α was significantly elevated in patients with influenza and COVID‐19, in which IL‐38 level was negatively and IL‐36α was positively associated with infection severity. Wang et al 50 showed elevated level of IL‐38 in patients with chronic hepatitis B, suggesting that IL‐38 could be used as a biomarker for liver hepatitis infection and liver injury 51 . Fazeli et al 52 reported that the level of IL‐38 was higher in healthy subjects than treated HCV‐infected patients, and HCV‐infected patients with higher levels of IL‐38 indicated less liver damage.…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…Wang et al 50 showed elevated level of IL‐38 in patients with chronic hepatitis B, suggesting that IL‐38 could be used as a biomarker for liver hepatitis infection and liver injury. 51 Fazeli et al 52 reported that the level of IL‐38 was higher in healthy subjects than treated HCV‐infected patients, and HCV‐infected patients with higher levels of IL‐38 indicated less liver damage. In sepsis mice model, the level of IL‐38 increased and IL‐38 could prolong the survival of mice.…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…In another study, immunobiological factors such as vitamin E, IL-17, IL-37, and IL-38 were assessed in Iraqi male patients with chronic hepatitis B (CHB). Although they reported diminished expression levels of IL-38 and vitamin E in patient groups compared to the healthy controls, they did not recommend monitoring concentrations of IL-38 for the identification of patients with CHB and the assessment of risk stratification [205].…”
Section: Role Of Il-38 In Infectious Diseases Hepatitismentioning
confidence: 98%
“…However, hyperthyroidism may cause abnormally low cholesterol levels or an improvement in lipid profile for no apparent reason [12]. Many Iraqi studies have examined the relationship between inflammatory variables and various diseases [13,14], but this study is the first to study the relationship of neudesin to thyroid dysfunction.…”
Section: Introductionmentioning
confidence: 95%